Arabidopsis Phosphatidic Acid Phosphohydrolases Are Essential for Growth under Nitrogen-Depleted Conditions - Yoshitake, Yushi; Sato, Ryoichi; Madoka, Yuka; Ikeda, Keiko; Murakawa, Masato; Suruga, Ko; Sugiura, Daisuke; Noguchi, Ko; Ohta, Hiroyuki; Shimojima, Mie (Frontiers in Plant Science, 2017)
The Arabidopsis homologs of mammalian lipin, PAH1 and PAH2, are cytosolic phosphatidic acid phosphohydrolases that are involved in phospholipid biosynthesis and are essential for growth under phosphate starvation. Here, pah1 pah2 double-knockout mutants were found to be hypersensitive to nitrogen (N) starvation, whereas transgenic plants overexpressing PAH1 or PAH2 in the pah1 pah2 mutant background showed a similar growth phenotype as compared with wild type (WT) under N starvation. The chlorophyll content of pah1 pah2 was significantly lower than that of WT, whereas the chlorophyll content and photosynthetic activity of the transgenic plants were significantly higher than those of WT under N-depleted conditions. Membrane glycerolipid composition of the pah1 pah2 mutants showed a significant decrease in the ratio of chloroplast lipids to other phospholipids, whereas membrane lipid composition did not differ between transgenic plants and WT plants. Pulse-chase labeling experiments using plants grown under N-depleted conditions showed that, in pah1 pah2 plants, the labeling ratio of chloroplast lipids such as phosphatidylglycerol and monogalactosyldiacylglycerol was significantly lower than in WT. Moreover, N starvation–induced degradation of chloroplast structure was enhanced in pah1 pah2 mutants, and the membrane structure was recovered by complementation with PAH1. Thus, PAH is involved in maintaining chloroplast membrane structure and is required for growth under N-depleted conditions.